Identification, proteolytic activity quantification and biofilm-forming characterization of Gram-positive, proteolytic, psychrotrophic bacteria isolated from cold raw milk - Zarei, Mehdi; Elmi Anvari, Sahar; Maktabi, Siavash; Saris, Per Erik Joakim; Yousefvand, Amin (PLOS ONE, 2023)
Psychrotrophic bacteria of raw milk face the dairy industry with significant spoilage and technological problems due to their ability to produce heat-resistant enzymes and biofilms. Despite extensive information about Gram-negative psychrotrophic bacteria in milk, little is known about Gram-positive psychrotrophic bacteria in milk, and their proteolytic activity and biofilm-forming characteristics. In the present study, Gram-positive, proteolytic, psychrotrophic bacteria of cold raw milk were identified, and their proteolytic activity and biofilm-forming capacity were quantified. In total, 12 genera and 22 species were represented among the bacterial isolates, however 50% belonged to three genera, namely Staphylococcus (19.4%), Bacillus (16.7%), and Enterococcus (13.9%). Different levels of proteolytic activity were detected in the identified isolates, even among the strains belonging to the same species. In addition, proteolytic activity was significantly higher at 25°C than at 7°C for all isolates. The crystal violet staining assay in polystyrene microtitre plates revealed a high level of variation in the biofilm-forming capacity at 7°C. After 72 hours of incubation, 11.1% of the strains did not produce a biofilm, while 27.8%, 52.8%, and 8.3% produced low, moderate, and high amounts of biofilm on polystyrene, respectively. The psychrotrophic bacteria were also able to produce biofilms on the surface of stainless steel coupons in ultra-high temperature milk after 72 h of incubation at 7°C; the number of attached cells ranged from 1.34 to 5.11 log cfu/cm2. These results expand the knowledge related to the proteolytic activity and biofilm-forming capacity of Gram-positive psychrotrophic milk bacteria.